2002
DOI: 10.1111/j.1582-4934.2002.tb00518.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in the pathogenesis of nonalcoholic fatty liver disease, in rats fed with a choline‐deficient diet

Abstract: Background Aim: The pathogenesis of Nonalcoholic Fatty Liver Disease remains largely unknown, but oxidative stress seems to be involved. The aim of this study was to evaluate the role of oxidative stress in experimental hepatic steatosis induced by a choline-deficient diet. Methods: Fatty liver disease was induced in Wistar rats by a cholinedeficient diet. The animals were randomized into three groups: I (G1) and II (G2), n=6 each -fed with a cholinedeficient diet for four and twelve weeks respectively; Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
8

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 23 publications
2
71
0
8
Order By: Relevance
“…This paper further recognizes that fat accumulation in the liver is associated with decreased efficiency of the phosphorylative system, in concordance with our previous studies in another animal model of fatty liver (Teodoro et al, 2006). Although other studies have been conducted with the choline-deficient model of fatty liver disease (Vendemiale et al, 2001;Oliveira et al, 2002;Grattagliano et al, 2003;Zafrani, 2004), this work proved invaluable since it is the first of its kind to apply a timeline approach. The mitochondrial function, mainly at the bioenergetic level, was found to be impaired due to fat accumulation.…”
Section: Samplesupporting
confidence: 87%
“…This paper further recognizes that fat accumulation in the liver is associated with decreased efficiency of the phosphorylative system, in concordance with our previous studies in another animal model of fatty liver (Teodoro et al, 2006). Although other studies have been conducted with the choline-deficient model of fatty liver disease (Vendemiale et al, 2001;Oliveira et al, 2002;Grattagliano et al, 2003;Zafrani, 2004), this work proved invaluable since it is the first of its kind to apply a timeline approach. The mitochondrial function, mainly at the bioenergetic level, was found to be impaired due to fat accumulation.…”
Section: Samplesupporting
confidence: 87%
“…In the present study, relative to choline deficiency, dietary choline supplementation markedly decreased pro-inflammatory cytokines IL-1b, TNF-a, IFN-g and IL-8 and increased anti-inflammatory cytokines IL-10 and TGFb1 mRNA levels in the gills of grass carp, suggesting that choline could reduce the inflammation in the gills of fish. Although research in rat has implied that choline could attenuate the liver inflammation [56], but the exact mechanisms which choline regulates the inflammation remains largely unknown. To our knowledge, production of cytokine could be regulated by the signaling pathway of TOR and NF-kB [12].…”
Section: Choline Supplementation Attenuated Inflammation In the Gillsmentioning
confidence: 99%
“…This fact may have occurred because hepatic fibrogenesis probably was not present, as observed by histological analysis. Oxidative stress occurring within a context of triacyglyceride deposition inside the hepatocytes appears to be important for the progression of steatosis to steatohepatitis and fribrosis (19,20) . Several studies have demonstrated that reactive oxygen species are increase in steatohepatitis, whereas antioxidant (vitamin E and glutathione) levels are decreased (10,11) .…”
Section: -Out/dez 2010mentioning
confidence: 99%